Transthoracic and transoesophageal echocardiography: a systematic review of feasibility and impact on diagnosis, management and outcome after cardiac surgery. (25th June 2016) - Heiberg, J.; El‐Ansary, D.; Royse, C. F.; Royse, A. G.; Alsaddique, A. A.; Canty, D. J.
Summary: Transthoracic and transoesophageal echocardiography are increasingly used as tools to improve clinical assessment following cardiac surgery. However, most physicians are not trained in echocardiography, and there is no widespread agreement on the feasibility, indications or effect on outcome of transthoracic or transoesophageal echocardiography for patients after cardiac surgery. We performed a systematic review of electronic databases for focused transthoracic and transoesophageal echocardiography after cardiac surgery which revealed 15 full‐text articles. They consistently reported that echocardiography is feasible, whether performed by a novice or expert, and frequently resulted in important changes in diagnosis of cardiac abnormalities and their management. However, most were observational studies and there were no well‐designed trials investigating the impact of echocardiography on outcome. We conclude that both transthoracic and transoesophageal echocardiography are useful following cardiac surgery.